Active immunization of cattle with a bothropic toxoid does not abrogate envenomation by Bothrops asper venom, but increases the likelihood of survival. (March 2017) - Herrera, María; González, Katherine; Rodríguez, Carlos; Gómez, Aarón; Segura, Álvaro; Vargas, Mariángela; Villalta, Mauren; Estrada, Ricardo; León, Guillermo
Abstract: This study assessed the protective effect of active immunization of cattle to prevent the envenomation induced by B. asper venom. Two groups of oxen were immunized with a bothropic toxoid and challenged by an intramuscular injection of either 10 or 50 mg B. asper venom, to induce moderate or severe envenomations, respectively. Non-immunized oxen were used as controls. It was found that immunized oxen developed local edema similar to those observed in non-immunized animals. However, systemic effects were totally prevented in immunized oxen challenged with 10 mg venom, and therefore antivenom treatment was not required. When immunized oxen were challenged with 50 mg venom, coagulopathy was manifested 3–16 h later than in non-immunized oxen, demonstrating a delay in the onset of systemic envenomation. In these animals, active immunization did not eliminate the need for antivenom treatment, but increased the time lapse in which antivenom administration is still effective. All experimentally envenomed oxen completely recovered after a week following venom injection. Our results suggest that immunization of cattle with a bothropic toxoid prevents the development of systemic effects in moderate envenomations by B. asper, but does not abrogate these effects in severe envenomation. Highlights: Bothrops asper causes most of the envenomations in cattle in Central America. The protective effect of active immunization with a bothropic toxoid was assessed. Active immunization of cattle does not prevent envenomation. Active immunization of cattle increases the likelihood of survival.